Recombinant human thrombopoietin in critically ill patients with sepsis-associated thrombocytopenia: A clinical study - Yu Liu; Gang Jin; Jingjing Sun; Xue Wang; Litao Guo (International Journal of Infectious Diseases, 2020)
Background: Sepsis causes varying degrees of thrombocytopenia that are closely related to the likelihood of patient mortality. This study analysed the effect of recombinant human thrombopoietin (rhTPO) on the platelet count in critically ill patients with sepsis-associated thrombocytopenia and provided a reference for its treatment. Material/methods: The study was a retrospective analysis of the clinical data of patients. Patients were divided into an rhTPO group and control group according to rhTPO use during treatment. Demographical and clinical data (age, sex, history of hypertension, diabetes, platelet counts, mortality rate, etc.) of the patients were collected and analysed using statistical software; p < 0.05 was considered statistically significant. Results: Of 213 patients, 84 constituted the rhTPO group and 129 constituted the control group. The increase in platelet counts was significantly higher in the rhTPO group than in the control group on the third day (43.01 ± 18.23 × 109/L vs. 36.31 ± 14.17 × 109/L, p = 0.003), fifth day (71.51 ± 39.59 × 109/L vs. 42.95 ± 20.48 × 109/L, p < 0.001) and seventh day (115.36 ± 69.41 × 109/L vs. 62.54 ± 42.70 × 109/L, p < 0.001). Further statistical analysis of the data of patients with platelet counts ≤30 × 109/L and >30 × 109/L and APACHE II scores >15 and ≤15 at the time of diagnosis showed that the increase in platelet counts in the rhTPO group was greater. There was no significant between-group difference in volume of platelet transfusions (rhTPO group 15.42 ± 17.20 vs. control group 10.93 ± 17.48, p = 0.068). The cost of ICU treatment in patients with rhTPO was higher (RMB 126,936.21 ± 86,548.27 vs. 101,685.28 ± 77,291.75, p = 0.027); however, the ICU stay time was shorter (9.20 ± 5.38 vs. 10.88 ± 6.82, p = 0.047). There was no significant difference in 28-day mortality (rhTPO group: 25.0% vs. control group: 34.1%, p = 0.158) between the two groups. Conclusion: For patients with severe thrombocytopenia or severe sepsis, rhTPO was efficacious in increasing their platelet counts, resulting in a shorter ICU stay time.